Workplace Violence and Job Outcomes of Newly Licensed Nurses - Hyoung Eun Chang, RN, MPH; Sung-Hyun Cho, RN, PhD (Elsevier, 2016)
Purpose: The purpose of this study was to examine the prevalence of workplace violence toward newly licensed nurses and the relationship between workplace violence and job outcomes. Methods: An online survey was conducted of newly licensed registered nurses who had obtained their license in 2012 or 2013 in South Korea and had been working for 5-12 months after first being employed. The sample consisted of 312 nurses working in hospitals or clinics. The Copenhagen Psychosocial Questionnaire II was used to measure violence and nurse job outcomes. Multiple linear and logistic regression analyses were conducted to examine the relationship between violence and job outcomes. Results: Verbal abuse was most prevalent (59.6%), followed by threats of violence (36.9%), physical violence (27.6%), bullying (25.6%), and sexual harassment (22.4%). Approximately three quarters of the nurses had experienced at least one type of violence. The main perpetrators were patients and nurse colleagues, although the distribution of perpetrators varied depending on the type of violence. Bullying had a significant relationship with all four job outcomes (job satisfaction, burnout, commitment to the workplace, and intent to leave), while verbal abuse was associated with all job outcomes except for intent to leave. Violence perpetrated by nurse colleagues had a significant relationship with all four job outcomes, while violence by physicians had a significant inverse relationship with job satisfaction. Conclusions: Workplace violence is experienced by a high percentage of newly licensed nurses, and is associated with their job outcomes.